(3ELGRI YeQ Hf YHO GdcQje Hf YHO GdQShd Gdecis - (3YeQ Hf YHO GdcQje Hf YHO GdQShd Gdecjs
(3ChdgG (B:s
(3GdMeO ddg GdPi GfRd GdSfI GdSfjI GdZQGA GVhA ef GdUHM GdGHdL ceG GfRd GMSf GdMOjK cJGHkG eJTGHgkG CeG HYO abO EdJeS efi GdTjN eMeO GSMb Hf eMeO GaVd GdOgdhi s
(3BNQgG (B:s
(3MJi JNJe eY NGJeI cd ShQI hbO SeY efi GdaGJMI hShQI GdUa GdYdGeI Ph GdGNdGb GdeQVjI hCSCd Gddg GdJhajb hMSf GdNJGe di hdg hddeSdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde abW s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdSYjOjI GdYGeI ` Jhfc (B((3GUhd MOjK (B39) s
Keywords: (3GdMOjK h GdeUWdMs